SYZYGIUM CUMINI REDUCES VCAM-1 EXPRESSION IN ENDOTHELIAL CELLS FROM PREECLAMPTIC PATIENTS - siswi wulandari; binti qoniah (Jurnal Kesehatan Madani Medika (JKMM), 2016)
The present study sought to investigate a role for Syzygium cumini on VCAM-1 expression in endothelial cells from preeclamptic patients. Endothelial cells were obtained from human umbilical vascular endothelial cells. At confluency, endothelial cells were divided into five groups, which included control (untreated), endothelial cells from preeclamptic patients (PP), endothelial cells exposed to PP in the presence of ethanolic extract of Syzygium cumini (PP + SC) at the following three doses: 100; 200; and 400 ppm. Analysis of VCAM-2 level were done by immunohistochemistry technically. This increase in VCAM-1 was significantly (P < 0.05) attenuated by both the 200 and 400 ppm treatments of Syzygium cumini extract. In conclusion, Syzygium cumini extract prohibits the increase in VCAM-1 and ICAM-1 in endothelial cells induced by plasma from preeclamptic patients. Therefore this may provide a natural therapy for attenuating the adhesion molecule induced by endothelial dysfunction found in this pregnancy complication